Study of static voltage stability index as an indicator for under voltage load shedding schemes - Zahidi R.A.; Abidin I.Z.; Hashim H.; Omar Y.R.; Ahmad N.; Ali A.M. (2023)
Under Voltage Load Shedding (UVLS) has been successfully deployed in many systems throughout the world to protect local systems from voltage collapse. This is particularly true if the system conditions and the contingencies leading to voltage instabilities are of low probability, but would result in serious consequences. However, the locations and how much load to shed requires expert knowledge and experience working with the power grid. This paper will present on utilizing an established index called FVSI (Fast Voltage Stability Index) to act as a numerical verification of the shedding locations. The research work done shows that the FVSI index can be used and load shedding at these points does improve the stability of the system.